Spatial knowledge and firefighters' wayfinding performance: A virtual reality search and rescue experiment. (July 2021) - Shi, Yangming; Kang, John; Xia, Pengxiang; Tyagi, Oshin; Mehta, Ranjana K.; Du, Jing
Highlights: This paper tests how spatial information affects firefighters' wayfinding performance. Virtual Reality based experiment (n = 40) was performed to examine three wayfinding methods. Results show that route information is more efficient for supporting wayfinding. The use of survey information or maps lead to polarization in path planning. The findings help design better wayfinding systems and training methods. Abstract: Firefighters often need to digest complex spatial information within a short period of time for search and rescue. Previous wayfinding literature has documented evidence about how the general population in normal situations leverage different forms of spatial information, including landmarks, routes and survey (maps), to develop spatial knowledge and guide wayfinding. However, little is known about how the arbitrarily given spatial information affects firefighter wayfinding behavior and performance when the time is limited and there is no privilege for them to develop complete spatial knowledge in an evolving manner. To narrow the knowledge gap, we conducted a wayfinding experiment with firefighters (n = 40) using Virtual Reality (VR). In the experiment, firefighters were required to find three victims in a simulated office maze. Each firefighter randomly experienced four experimental conditions in this study including control condition, landmark condition, route condition, and survey (map) condition. For each experimental condition, firefighters had 3 min to memorize the different layouts of the virtual office mazes using one of three spatial information including landmarks, routes, and survey (map), and then went to the virtual office maze to find the victims. The number of victims found, time, and navigation patterns were used to evaluate firefighters' wayfinding performance. The results indicated that the route and survey spatial information was more efficient in facilitating firefighter to memorize the layout, leading to a better wayfinding performance. We also found that although the survey information provided more complete information about the layout, it also burdened firefighters in a way that they had to plan the path with limited time. Since survey information may induce different path planning strategies, survey information did not result in a better performance than the route information as suggested by previous studies. This research helps explain the relationship between different forms of spatial information and the wayfinding performance of firefighters. The findings will help professionals design better training protocols and technologies for firefighters.